Q: What is 4a 2b a?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

Related questions

2b+b-4

4a + 3c - 2b - c + a - b = 5a - 3b + 2c

4a+2b-1a+9b combine all alike variables using commutative property of addition 4a-1a+2b+9b Then add the like variables 3a+11b

a-b+a-b+2b+a = 4a

Assuming the missing sign is "minus" then you have the difference between two squares. This is solved as (x + y)(x - y). In your example x = 4a and y = 2b so the factorisation is (4a + 2b)(4a - 2b) or more completely: (4)(2a + b)(2a - b).

3a - 2b

a+a+a+a+b+b - add the like terms =4a+2b 4a and 2b cannot be added because they are not like terms.

6 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -36 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -36 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -36 is the average of 2a and a - 2b so 12 = 2a + a - 2b = 3a - 2b3 is the average of 2a - b and 4a + 3b so 6 = 2a - b + 4a + 3b = 6a + 2bAdding the two equations gives: 18 = 9a so that a = 2Substituting for a in the first gives 12 = 6 - 2b so that b = -3

10a - 10 b

= 4a2 + 2ab 2b2

4(a + 2b - 4c)

7a-2b